PENGENALAN BUDAYA ENTREPRENEURSHIP YANG MENINGKATKAN LAYANAN DAN PENYUSUNAN LAPORAN KEUANGAN SEDERHANA PADA USAHA JASA LAUNDRY DI PENGADEGAN (UMKM) - Anarsyah, Rining Tyias Putri; Utami, Putri Kardella; Nurhikmah, Meila; Rahmadi , Zara Tania; dharma , Dias Adi (PUAN INDONESIA, 2025)
This Community Service program aims to introduce the culture of entrepreneurship and improve the quality of service and the ability to prepare simple financial reports for micro, small, and medium-sized enterprises (MSMEs) in the laundry service sector in Pengadegan. Based on observations, laundry business owners in this area generally have not optimized the potential of their services and financial management in a structured manner, which affects the competitiveness of their businesses. This program includes training and mentoring activities, covering the introduction of basic entrepreneurship principles, strategies for improving customer service, and techniques for preparing simple financial reports such as daily transaction records, cash inflows and outflows, and profit-loss calculations. The method of implementation for this activity involves conducting interviews, observations, and mentoring in preparing simple financial reports. Data was obtained after conducting interviews with MSME laundry businesses. The results of this program show an improvement in MSME owners' understanding of the importance of service innovation and transparent financial management. The activity has had a positive impact on business management capabilities and successfully enhanced the understanding of MSME laundry owners in Pengadegan regarding the culture of entrepreneurship, customer service quality, and preparation of simple financial reports. Additionally, 80% of MSME owners at Via Laundry were able to independently prepare simple financial reports after the mentoring. With proper implementation, this program is expected to help MSME laundry services improve operational efficiency and the sustainability of their businesses in the increasingly competitive market Keywords— Entrepreneurship Culture, Simple Financial Reports, MSMEs (Micro, Small, and Medium Enterprises)